RISK MANAGEMENT OF PROCUREMENT PROCESSES IN AUTOMOTIVE SUPPLY CHAIN; BAHMAN MOTOR COMPANY - Nahavandi, Nasim; Tavakoli, Parizad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
Supply chain risk management is one of the issues that are considered in the field of supply chain management, and its importance is increasing every day. The automobile industry is one of the vital industries in every country, and the risks of that must be given special attention. The main purpose of this research is to identify, assess, and respond to the procurement risks of the Bahman Motor Company. In the first step, 31 risks were identified and then were prioritized by FMEA and FMEA-TOPSIS methods. The results show that "Lack of timely providing of imported parts," "Failure to timely providing," "Impossibility to provide imported parts," "Failure/Delay in timely clearance of goods" are top risks. In this paper, a Three-Dimensional decision model is proposed to present response strategies to the risks, and the new controls were suggested that helps managers to make better decisions about allocating funds and resources for risks.